SOCIAL ORIENTATION AND TASK ORIENTATION IN CHILDREN - Nakayama, Kanjiro (Kyōiku Shinrigaku Kenkyū, 1983)
In this study, it was assumed that motivational trait of children could be made of two kinds of orientation: social orientation and task-orientation. The social orientation was defined by a willingness to participate in socially visible works, whereeas the task-orientation was defined by an interest in the independent mastery and the challenge to the difficulty. The purpose of this study was to construct a scale to measure the relative intensity of these orientations, and to investigate how these orientations relate to the children's adjustment to various situations. In the first study, a scale (originally containing 24 items) measuring the two orientations was constructed and administered to 436 boys and girls from 4 th to 9 th grade. The results indicated that in both elementary school and secondary school, two factors were obtained and the factor structure was very similar in both schools. As expected, these factors corresponded to the social and task-orientation. Consequently, the scale was of 16 items (8 items in each orientation). Next, the developmental trends in each orientation were analysed. The social orientation decreased at the 8 th grade level, and temporally increased in 6th grade boys. As for the task-orientation, a decrease was observed in girls, especially on items measuring challenge. In the second study, the relationships of the two orientations in children's adjustment were investigated. The measures were sociometric test (choice of playmates and study-mates),“l'épreuve du dynamisme évolutif”, self-esteem scale, and academic achievement. 180 boys and girls in 4 th through 6 th grade were used as subjects, and were classified into four categories according to their relative intensity of the two orientations. Main results were as follows. 1. In the sociometric status of each group, social orientation was related to the status in the choice of playmates, whereas both social and task-orientation were related to the status in the study-mates. Socially oriented groups showed relatively high rate of mutual choice. 2. In l'épreuve du dynamisme évolutif and the selfesteem scale, the socially oriented groups rated their feeling of social adjustment higher, and preferred their own school age more than the less oriented groups. 3. In the academic achievement, both orientations were related to some extent to their achievement in many school subjects. In general, the task-orientation had stronger relations; still, some characteristics in each subject were found. Some implications assuming two kinds of orientation (i. e. social and task-orientation) were discussed.